The Intelligent Monitoring Technology for Machining Thin-Walled Components: A Review - Gaoqun Liu; Yufeng Wang; Binda Huang; Wenfeng Ding (Machines)
Thin-walled components are extensively utilized in the aviation, aerospace, shipping, and nuclear energy industries due to their advantages of being lightweight and easily integrated. With an increased design quality and complexity of structures, thin-walled components have rendered traditional offline machining state prediction techniques inadequate for meeting the rising demands for machining quality. In recent years, advancements in intelligent manufacturing have led to the emergence of intelligent monitoring technologies that offer new solutions for enhancing the machining quality. This review categorizes technologies into online signal collection, state recognition, and intelligent decision-making, based on the implementation processes of intelligent monitoring. It summarizes the roles and current development status of various technologies within intelligent monitoring and outlines the existing challenges associated with each technology. Finally, the review discusses the challenges and future development trends of intelligent monitoring technology.